An innovative procedure for characterising a coupled elastoplastic damage model of behaviour using the Virtual Fields Method. (September 2015) - Notta-Cuvier, D.; Langrand, B.; Lauro, F.; Markiewicz, E.
Abstract: The characterisation of material behaviour models can be challenging, especially when dealing with strongly non-linear constitutive laws. Classical procedures are restricted to the treatment of homogeneous mechanical fields. They can therefore not be applied after strain localisation and behaviour model can be characterised only over a very limited strain range. In addition, several tests are generally needed to characterise complex behaviour models. On the contrary, the Virtual Fields Method (VFM) enables the treatment of inhomogeneous mechanical fields. The VFM therefore allows to take advantage of the increasingly powerful full-field measurement techniques. Moreover, its ability to process data enriched by heterogeneities can be used to significantly decrease the number of tests that are required for the identification of complex behaviours. In this paper, the VFM is developed for the characterisation of a fully coupled elastoplastic-damage behaviour model, using one uniaxial tensile test only. The process of identification is assessed using two kinds of thin-specimen geometries (numerically simulated strain fields). Results demonstrate the efficiency of the VFM for the simultaneous identification of plastic and damage parameters from a unique uniaxial tensile test, but also highlight that the definition of a suitable specimen geometry is a key factor for result accuracy.